Association of extent of resection on recurrence-free survival and functional outcome in vestibular schwannoma of the elderly - Wang, Sophie Shih-Yüng; Machetanz, Kathrin; Ebner, Florian; Naros, Georgios; Tatagiba, Marcos (Frontiers in Oncology, 2023)
Background: Despite the ongoing debate on the risk-benefit-ratio of vestibular schwannoma (VS) treatment options, watchful observation and radiation are usually favored in the Elderly (>65 years). If surgery is inevitable, a multimodal approach after deliberate subtotal resection has been suggested. The relationship between extent-of-resection (EOR) of surgical, functional outcome and the recurrence-free-survival (RFS) remains unclear. This present study aims to evaluate functional outcome and RFS of the Elderly in relation to EOR. Methods: This matched cohort study analyzed all consecutive Elderly VS patients treated at a tertiary referral center since 2005. A separate cohort (<65 years) served as a matched control group (Young). Clinical status was assessed by the Charlson Comorbidity Index (CCI), the Karnofsky Performance (KPS), the Gardner&Robertson (G&R) and the House&Brackmann (H&B) scales. RFS was evaluated MR-radiographically and Kaplan-Meier analysis. Results: Among 2,191 patients, 296 (14%) patients were classified as Elderly, of whom 133 (41%) were treated surgically. The Elderly were characterized by a higher preoperative morbidity and worse gait uncertainty. Postoperative mortality (0.8% and 1%), morbidity (13% and 14%) and functional outcome (G&R, H&B, KPS) did not differ between the Elderly and the Young. There was a significant benefit in regard to the preoperative imbalance. Gross total resection was accomplished in 74% of all cases. Lower grades of EOR (subtotal and decompressive surgery) raised the incidence of recurrence significantly. Conclusions: Surgical VS treatment aiming for complete tumor resection is feasible and safe, even in advanced age. A higher EOR is not associated with cranial nerve deterioration. In contrast, EOR determines recurrence-free-survival and the incidence of recurrence/progression in both study cohorts. The present study implies that subtotal VS resection without adjuvant therapy is not recommended. If surgery is indicated in the Elderly, gross total resection should be intended and if only subtotal resection is achieved, further adjuvant therapy e.g. radiotherapy should be discussed in this specific patient group.